Photosensitive resin composition, photosensitive resin film, pattern formation method, and light-emitting element
Patent Information
- Application Number
- JP2022160787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-10-05
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-10-05
AI Technical Summary
Existing methods for forming color conversion structures in micro-LED displays face challenges in miniaturization and achieving high lithography resolution and luminescent properties, particularly in adapting to small displays with improved light emitting characteristics.
A photosensitive resin composition comprising a resin with (meth)acryloyl groups, a photoradical generator, and quantum dots with a surface coating layer containing siloxane, which enhances lithography resolution and luminescent properties, preventing quantum dot fallout during development.
The composition allows for the formation of films with high resolution and good luminescent properties, enabling fine pattern formation and reliable light emission characteristics suitable for micro-LED displays.
Abstract
Description
[Technical field]
[0001] The present invention relates to a photosensitive resin composition, a photosensitive resin film using the photosensitive resin composition, a pattern forming method, and a light-emitting device. [Background technology]
[0002] Various methods have been proposed to create displays with red, green and blue subpixels. One method involves converting the light from an LED array from shorter wavelengths, blue, to longer wavelengths, red and green, through a color conversion structure, using quantum dots.
[0003] In recent years, LED arrays have become micro-sized, and micro LED displays using these have been attracting attention. One method for forming a color conversion structure on an LED array is a lithography process using a photosensitive material (Patent Document 1), but in recent years, further miniaturization is required for application to small displays. In addition, there are high demands for light emission characteristics in terms of display clarity. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-089347 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a photosensitive resin composition capable of easily forming a film having high lithography resolution and good light-emitting properties, a photosensitive resin film obtained using the photosensitive resin composition, a pattern forming method using the same, and a light-emitting element obtained using the photosensitive resin composition. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention provides a photosensitive resin composition, comprising: (A) a resin having a (meth)acryloyl group, (B) a photoradical generator, and (C) Quantum dots The quantum dots have a surface coating layer containing siloxane.
[0007] Such a photosensitive resin composition can easily form a film having high lithography resolution and good light emitting properties.
[0008] In the present invention, the component (C) preferably contains a skeleton having a (meth)acryloyl group in the surface coating layer.
[0009] Such a photosensitive resin composition can prevent the quantum dots from escaping during development, and can provide a pattern with high light-emitting properties.
[0010] In the present invention, it is preferable that the quantum dots of the component (C) have ligands coordinated to their surfaces, the surface coating layer contains siloxane bonds bonded to the ligands, and the substituents of the ligands have one or more of an amino group, a thiol group, a carboxy group, a phosphino group, a phosphine oxide group, and an ammonium ion.
[0011] Quantum dots having such ligands are preferred because they are easily coordinated to the surface.
[0012] In the present invention, the photosensitive resin composition preferably contains the component (C) in an amount of 5 to 80% by mass.
[0013] Such a photosensitive resin composition makes it possible to form a fine pattern while maintaining good light emitting properties.
[0014] In the present invention, the double bond equivalent of the component (A) is preferably 240 to 1,000 g / mol.
[0015] Such a photosensitive resin composition has a high crosslink density and can form a pattern with a good shape after development.
[0016] In the present invention, the weight average molecular weight Mw of the component (A) is preferably 5,000 to 100,000 g / mol.
[0017] With such a photosensitive resin composition, the film thickness of the exposed area is less likely to be reduced during development, and the solubility of the unexposed area is good.
[0018] In the present invention, it is preferable that the composition further contains a surfactant (D).
[0019] Such a photosensitive resin composition can improve the coatability.
[0020] In the present invention, it is preferable that the composition further contains a silane coupling agent (E).
[0021] Such a photosensitive resin composition can improve the adhesion to a substrate.
[0022] In the present invention, it is preferable that the composition further contains (F) a crosslinking agent having two or more functional (meth)acryloyl groups.
[0023] If such a photosensitive resin composition is used, the resulting cured film will have high reliability.
[0024] In the present invention, it is preferable that the composition further contains a solvent (G).
[0025] Such a photosensitive resin composition can improve the coatability.
[0026] The present invention also provides a photosensitive resin film which is a dried product of the above-described photosensitive resin composition.
[0027] Such a photosensitive resin film has high lithography resolution and good light emitting properties.
[0028] The present invention also provides a pattern forming method, comprising the steps of: (i) applying the above-described photosensitive resin composition onto a substrate to form a photosensitive resin film on the substrate; (ii) exposing the photosensitive resin film to light; and (iii) A step of developing the exposed photosensitive resin film with a developer to dissolve and remove the non-exposed areas to form a pattern. The present invention provides a pattern forming method comprising the steps of:
[0029] Such a pattern formation method makes it possible to form a pattern with high lithographic resolution, and to obtain a film pattern having good light-emitting properties.
[0030] The present invention also provides a light-emitting device comprising a cured coating obtained by the above-described pattern formation method.
[0031] Such a light emitting element has high lithography resolution and good light emitting characteristics. Effect of the Invention
[0032] The photosensitive resin composition of the present invention contains a resin having a (meth)acryloyl group, a photoradical generator, and quantum dots having a specific surface coating layer, and therefore can easily form a film having high resolution and good light-emitting properties, and is therefore suitable for light-emitting devices. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] As described above, there has been a demand for the development of a photosensitive resin composition capable of easily forming a film having high lithography resolution and good light-emitting properties, a photosensitive resin film obtained using the photosensitive resin composition, a pattern formation method using the same, and a light-emitting element obtained using the photosensitive resin composition.
[0034] Means for Solving the Problems The present inventors have conducted intensive research in order to achieve the above-mentioned object, and as a result have found that a photosensitive resin composition comprising (A) a resin having a (meth)acryloyl group, (B) a photoradical generator, and (C) quantum dots, wherein the quantum dots have a surface coating layer containing siloxane, has high lithography resolution and can easily form a film (photosensitive resin film) having good luminescence properties, thereby completing the present invention.
[0035] That is, the present invention is a photosensitive resin composition, (A) a resin having a (meth)acryloyl group, (B) a photoradical generator, and (C) Quantum dots wherein the quantum dots have a surface coating layer containing siloxane.
[0036] The present invention will be described in detail below, but the present invention is not limited thereto.
[0037] [Photosensitive resin composition] The photosensitive resin composition of the present invention contains (A) a resin having a (meth)acryloyl group, (B) a photoradical generator, and (C) a quantum dot having a specific surface coating layer. If necessary, it may further contain other components such as (D) a surfactant, (E) a silane coupling agent, (F) a crosslinking agent having two or more (meth)acryloyl groups, and (G) a solvent. Each component constituting the photosensitive resin composition will be described below.
[0038] [(A) Resin having a (meth)acryloyl group] The (A) resin having a (meth)acryloyl group used in the present invention is not particularly limited as long as it has a (meth)acryloyl group.
[0039] In the present invention, the weight average molecular weight Mw of the resin (A) having a (meth)acryloyl group is preferably in the range of 5,000 to 100,000 g / mol, more preferably in the range of 10,000 to 50,000 g / mol. If the weight average molecular weight of the resin (A) having a (meth)acryloyl group is within the above range, the film is less likely to be reduced in the exposed area during development, and the solubility of the non-exposed area is good. The weight average molecular weight is a value obtained as a weight average molecular weight (weight average degree of polymerization) converted into polystyrene by GPC (gel permeation chromatography) analysis using toluene as a developing solvent.
[0040] In the present invention, the (A) resin having a (meth)acryloyl group preferably has a double bond equivalent in the range of 240 to 1,000 g / mol, more preferably in the range of 240 to 700 g / mol. The double bond equivalent is the weight of the resin per acrylic group. If the (A) resin having a (meth)acryloyl group has a double bond equivalent in the above range, a pattern having a high crosslink density and a good shape after development can be formed.
[0041] In the present invention, the (A) resin having a (meth)acryloyl group preferably has an acid value in the range of 0 to 150 mgKOH / g. If the acid value is less than 30 mgKOH / g, the solubility in an alkaline developer is low, so development with an organic solvent is preferable. If the acid value is 150 mgKOH / g or less, the pattern does not peel off during alkaline development.
[0042] In the present invention, the (A) resin having a (meth)acryloyl group may be used alone or in combination of two or more kinds. The (A) resin having a (meth)acryloyl group is preferably in the range of 10 to 90 mass % relative to the total amount of the photosensitive resin composition. More preferably, it is in the range of 15 to 85 mass %.
[0043] [(B) Photoradical generator] The photoradical generator used in the present invention is not particularly limited, but examples thereof include acetophenone-based compounds, benzophenone-based compounds, thioxanthone-based compounds, benzoin-based compounds, triazine-based compounds, and oxime-based compounds.
[0044] Examples of acetophenone compounds include 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone, pt-butyltrichloroacetophenone, pt-butyldichloroacetophenone, 4-chloroacetophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one.
[0045] Examples of benzophenone-based compounds include benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 4,4'-dimethylaminobenzophenone, 4,4'-dichlorobenzophenone, and 3,3'-dimethyl-2-methoxybenzophenone.
[0046] Examples of thioxanthone compounds include thioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and 2-chlorothioxanthone.
[0047] Examples of the benzoin compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and benzyl dimethyl ketal.
[0048] Examples of triazine compounds include 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine. 2-biphenyl-4,6-bis(trichloromethyl)-s-triazine, bis(trichloromethyl)-6-styryl-s-triazine, 2-(naphth-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphth-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-piperonyl-s-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-s-triazine, and the like.
[0049] Examples of oxime compounds include 1,2-octanedione, O-acyloxime compounds, 2-(O-benzoyloxime)-1-[4-(phenylthio)phenyl]-1,2-octanedione, 1-(O-acetyloxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone, and O-ethoxycarbonyl-α-oxyamino-1-phenylpropan-1-one. Specific examples of O-acyloxime compounds include 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, 1-(4-phenylsulfanylphenyl)-butane-1,2-dione-2-oxime-O-benzoate, 1-(4-phenylsulfanylphenyl)-octane-1,2-dione-2-oxime-O-benzoate, 1-(4-phenylsulfanylphenyl)-octane-1-one oxime-O-acetate, and 1-(4-phenylsulfanylphenyl)-butan-1-one oxime-O-acetate.
[0050] In addition to the above compounds, the (B) photoradical generator may also include carbazole compounds, diketone compounds, sulfonium borate compounds, diazo compounds, imidazole compounds, non-imidazole compounds, and fluorene compounds.
[0051] The content of the photoradical generator (B) is preferably in the range of 0.1 to 10% by mass, more preferably in the range of 0.5 to 6% by mass, based on the total amount of the photosensitive resin composition. When the content of the photoradical generator is within the above range, a pattern with excellent resolution and excellent balance between sensitivity and developability during exposure without residual film can be obtained. The photoradical generator may be used alone or in combination of two or more kinds.
[0052] [(C) Quantum dots with specific surface coating layers] Quantum dots are nano-sized semiconductor materials. Atoms form molecules, and molecules form small molecular aggregates called clusters to form nanoparticles. When such nanoparticles show semiconductor properties, they are called quantum dots (quantum dot particles).
[0053] When a quantum dot receives energy from the outside and reaches an elevated state, it autonomously emits energy (emits light) according to the corresponding energy band gap.
[0054] The quantum dots (C) used in the present invention are not particularly limited as long as they have a surface coating layer containing siloxane, and can be used in any form. Quantum dots are mainly nanoparticles of 10 nm or less, but they may be nanowires, nanorods, nanotubes, nanocubes, etc., and any shape can be applied. In the present invention, the average particle size of the quantum dots was determined by directly observing at least 20 particles using a transmission electron microscope (TEM), calculating the diameter of a circle having the same area as the projected area of the particle, and using the average value.
[0055] The quantum dots (C) used in the present invention may be any suitable material, for example, a semiconductor material selected from the group consisting of II-VI group, III-V group, IV group, IV-VI group, I-III-VI group, II-IV-V group, mixed crystals or alloys thereof, or compounds having a perovskite structure. Specifically, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, Si, Ge, Sn, Pb, PbS, PbSe, PbTe, SnS, SnSe, SnTe, AgGaS 2 , AgInS 2 , AgGaSe 2 , AgInSe 2 , CuGaS 2 , CuGaSe 2 , CuInS 2 , CuInSe 2 , ZnSiP 2 , ZnGeP 2 , CdSiP 2 , CdGeP 2 , CsPbCl 3 , CsPbBr 3 , CsPbI 3 , CsSnCl 3 , CsSnBr 3 , CsSnI 3 These include, but are not limited to, compounds comprising:
[0056] The quantum dots (C) used in the present invention can have a core-shell structure. The shell material capable of forming the core-shell structure is not particularly limited, but is preferably one having a large band gap and low lattice mismatch with respect to the core material, and can be arbitrarily combined according to the core material. Specific shell materials include ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, BeS, BeSe, BeTe, MgS, MgSe, MgTe, PbS, PbSe, PbTe, SnS, SnSe, SnTe, CuF, CuCl, CuBr, CuI, etc., and the above materials may be selected as a single or multiple mixed crystals, but are not limited thereto.
[0057] There are various methods for producing the quantum dots (C) used in the present invention, such as a liquid phase method or a gas phase method, and the method is not particularly limited in the present invention. However, from the viewpoint of exhibiting high fluorescence emission efficiency, it is preferable to use semiconductor nanoparticles obtained by a hot soap method or a hot injection method, in which a precursor species is reacted at high temperature in a nonpolar solvent with a high boiling point, and it is desirable that an organic ligand is coordinated to the surface in order to impart dispersibility in the nonpolar solvent and reduce surface defects.
[0058] From the viewpoint of dispersibility, the organic ligand preferably contains an aliphatic hydrocarbon. Examples of such organic ligands include oleic acid, stearic acid, palmitic acid, myristic acid, lauric acid, decanoic acid, octanoic acid, oleylamine, stearyl (octadecyl)amine, dodecyl (lauryl)amine, decylamine, octylamine, octadecanethiol, hexadecanethiol, tetradecanethiol, dodecanethiol, decanethiol, octanethiol, trioctylphosphine, trioctylphosphine oxide, triphenylphosphine, triphenylphosphine oxide, tributylphosphine, and tributylphosphine oxide, and the like, and these may be used alone or in combination.
[0059] In addition to the organic ligands, the (C) quantum dots used in the present invention are coordinated with ligands having a substituent capable of forming a siloxane bond. As the ligand having a substituent capable of forming a siloxane bond, it is preferable that the ligand has a substituent that interacts with or is adsorbed on the quantum dot surface. Examples of the substituent that interacts with or is adsorbed on the quantum dot surface include amino groups, thiol groups, carboxy groups, mercapto groups, phosphino groups, phosphine groups, phosphine oxide groups, sulfonyl groups, ammonium ions, and quaternary ammonium salts, among which amino groups, carboxy groups, mercapto groups, phosphine groups, and quaternary ammonium salts are preferred from the viewpoint of the strength of coordination.
[0060] The quantum dots (C) used in the present invention have a quantum dot surface coated with siloxane. Therefore, the ligand having a substituent that interacts with or adsorbs to the quantum dot surface has a substituent that can form a siloxane bond. Examples of the substituent that can form a siloxane bond include compounds containing alkoxysilanes such as trimethoxysilyl groups, triethoxysilyl groups, dimethoxymethylsilyl groups, diethoxymethylsilyl groups, dimethylmethoxysilyl groups, and ethoxydimethylsilyl groups, compounds having silazane bonds, compounds having Si-OH bonds, compounds having Si-X (X: halogen) bonds, and carboxylic acids. However, it is preferable to use ligands containing alkoxysilanes, silazane, and Si-OH because the reaction can proceed under mild conditions in which no acid is generated as a by-product of the reaction. Phenyl-containing siloxanes can be formed by reacting these with diphenyldisilanol or the like.
[0061] The amount of siloxane coating is not particularly limited, but is preferably in the range of 1 to 50% by mass, and more preferably in the range of 5 to 30% by mass. If the amount of siloxane coating is too large, the quantum dot content decreases, but if it is within the above range, it is possible to improve dispersibility in the base polymer and suppress deterioration of the quantum dots during exposure.
[0062] The quantum dots (C) used in the present invention may further include a skeleton having a (meth)acryloyl group in the surface coating layer.
[0063] By introducing a (meth)acryloyl group into the surface coating layer, the (A) resin having a (meth)acryloyl group crosslinks with the surface coating layer after exposure, suppressing the quantum dots from escaping during development and obtaining a pattern with high luminescence properties. In addition, compatibility with the (A) resin having a (meth)acryloyl group is improved, suppressing the generation of aggregates when the photosensitive resin composition is prepared.
[0064] The quantum dots (C) used in the present invention are preferably 5 to 80% by mass, more preferably 10 to 70% by mass, based on the total amount of the photosensitive resin composition. If the content of the quantum dot particles is within the above range, fine patterns can be formed while maintaining good light-emitting properties.
[0065] The method of introducing the (meth)acryloyl group into the (C) component and the amount of introduction are not particularly limited, but when forming the phenyl group-containing siloxane, a method of adding a previously prepared skeleton having a (meth)acryloyl group containing an alkoxysilane and reacting it, or a method of directly introducing a skeleton having a (meth)acryloyl group by a radical reaction, etc. The amount of introduction may be appropriately adjusted in consideration of compatibility with the resin.
[0066] [(D) Surfactant] The photosensitive resin composition of the present invention may further contain a surfactant (D) in order to improve the coatability.
[0067] Examples of the surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene sterial ether, polyoxyethylene cetyl ether, and polyoxyethylene olein ether; polyoxyethylene alkyl allyl ethers such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether; polyoxyethylene polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, and sorbitan monostearate; polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyether silicone, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan tristearate. nonionic surfactants of polyoxyethylene sorbitan fatty acid esters such as sorbitol, EFTOP EF301, EF303, EF352 (manufactured by Tochem Products Co., Ltd.), Megafac F171, F172, F173 (manufactured by DIC Corporation), Fluorad FC-4430, FC-430, FC-431 (manufactured by Sumitomo 3M Limited), Surfynol E1004 (manufactured by Nissin Chemical Industry Co., Ltd.), Asahiguard AG710, Surflon S-381, Examples of such surfactants include fluorosurfactants such as S-382, SC101, SC102, SC103, SC104, SC105, SC106, KH-10, KH-20, KH-30, and KH-40 (manufactured by AGC Seimi Chemical Co., Ltd.), organosiloxane polymers KP-341, X-70-092, and X-70-093 (manufactured by Shin-Etsu Chemical Co., Ltd.), and acrylic acid- or methacrylic acid-based Polyflow No. 75 and No. 95 (manufactured by Kyoeisha Chemical Co., Ltd.).
[0068] The amount of the surfactant (D) is preferably 0.01 to 3 mass %, more preferably 0.02 to 1 mass %, based on the total amount of the photosensitive resin composition. These can be used alone or in combination of two or more kinds.
[0069] [(E) Silane coupling agent] The photosensitive resin composition of the present invention may further contain (E) a silane coupling agent in order to improve adhesion to a substrate.
[0070] Examples of the silane coupling agent include amino group-containing silane coupling agents, epoxy group-containing silane coupling agents, (meth)acryloyl group-containing silane coupling agents, mercapto group-containing silane coupling agents, vinyl group-containing silane coupling agents, ureido group-containing silane coupling agents, sulfide group-containing silane coupling agents, and silane coupling agents having a cyclic anhydride structure. Among these, (meth)acryloyl group-containing silane coupling agents are preferred.
[0071] Examples of the (meth)acryloyl group-containing silane coupling agent include KBM-502, KBM-503, KBE-502, KBE-503, and KBM-5103 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0072] The amount of the silane coupling agent (E) is preferably 0.01 to 5 mass %, more preferably 0.05 to 4 mass %, based on the total amount of the photosensitive resin composition. These may be used alone or in combination of two or more.
[0073] [(F) Crosslinking agent] The photosensitive resin composition of the present invention may further contain a crosslinking agent (F). The crosslinking agent is a component that undergoes a crosslinking reaction with the resin (A) having a (meth)acryloyl group and the surface coating layer of the quantum dots (C) to facilitate the formation of a pattern with a good shape, and therefore a crosslinking agent having two or more functional (meth)acryloyl groups is preferred.
[0074] Examples of crosslinking agents having two or more functional (meth)acryloyl groups include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexane glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin di(meth)acrylate, and the like. acrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2 -bis(4-(meth)acryloxypolyethoxyphenyl)propane, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, ethylene glycol diglycidyl ether di(meth)acrylate, diethylene glycol diglycidyl ether di(meth)acrylate, phthalic acid diglycidyl ester di(meth)acrylate, glycerin triacrylate, glycerin polyglycidyl ether poly(meth)acrylate, urethane (meth)acrylate (i.e., a reaction product of tolylene diisocyanate, trimethylhexamethylene diisocyanate, hexamethylene diisocyanate, or the like with 2-hydroxyethyl (meth)acrylate), methylene bis(meth)acrylamide, (meth)acrylamide methylene ether, a condensation product of a polyhydric alcohol and N-methylol (meth)acrylamide, and the like polyfunctional monomers, and triacryl formal, and the like.
[0075] The amount of the crosslinking agent (F) is preferably 0.5 to 100 parts by mass, and more preferably 1 to 50 parts by mass, per 100 parts by mass of the component (A). These may be used alone or in combination of two or more kinds.
[0076] [(G) Solvent] The photosensitive resin composition of the present invention may contain a solvent as component (G). The solvent (G) is not particularly limited as long as it can dissolve and disperse the above-mentioned components (A) to (F) and other various additives.
[0077] As the (G) solvent, organic solvents are preferred, for example, ketones such as cyclohexanone, cyclopentanone, methyl-2-n-pentyl ketone, etc.; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, etc.; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, diethylene glycol dimethyl ether, etc.; esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, propylene glycol-mono-tert-butyl ether acetate, γ-butyrolactone, etc. These may be used alone or in combination of two or more.
[0078] As the (G) solvent, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, cyclopentanone, and mixed solvents thereof are preferable, which have excellent solubility for the (A) resin having a (meth)acryloyl group and the (B) photoradical generator.
[0079] From the viewpoints of compatibility and viscosity of the photosensitive resin composition, the content of the component (G) is preferably from 25 to 85 mass %, and more preferably from 35 to 75 mass %, based on the total amount of the photosensitive resin composition.
[0080] [Photosensitive resin film] The photosensitive resin film of the present invention is a dried product of the above-described photosensitive resin composition.
[0081] [Pattern formation method using photosensitive resin composition] The pattern forming method using the photosensitive resin composition of the present invention comprises the steps of: (i) applying the above-described photosensitive resin composition onto a substrate to form a photosensitive resin film on the substrate; (ii) exposing the photosensitive resin film to light; and (iii) developing the exposed photosensitive resin film with a developer Includes.
[0082] Step (i) is a step of applying the above-described photosensitive resin composition onto a substrate to form a photosensitive resin film on the substrate. The photosensitive resin film is a dried product of the above-described photosensitive resin composition. Examples of the substrate include silicon wafers, glass wafers, quartz wafers, plastic circuit boards, and ceramic circuit boards.
[0083] The coating method may be a known method, such as a dipping method, a spin coating method, a roll coating method, etc. The coating amount can be appropriately selected depending on the purpose, but it is preferable to coat so that the thickness of the obtained photosensitive resin film (dried product of the photosensitive resin composition) is preferably 0.1 to 200 μm, more preferably 1 to 150 μm.
[0084] Here, in order to efficiently carry out the photocuring reaction, the solvent and the like may be evaporated in advance by preheating (prebaking) as necessary. The prebaking can be carried out, for example, at 40 to 140° C. for about 1 minute to 1 hour.
[0085] Next, (ii) the photosensitive resin film is exposed to light. In this case, the exposure is preferably performed with light having a wavelength of 10 to 600 nm, and more preferably with light having a wavelength of 190 to 500 nm. Examples of light having such wavelengths include light of various wavelengths generated by a radiation generator, such as ultraviolet light such as g-line, h-line, and i-line, and far ultraviolet light (248 nm, 193 nm). Of these, light having a wavelength of 248 to 436 nm is particularly preferred. The exposure dose is 10 to 10,000 mJ / cm. 2 is preferred.
[0086] The exposure may be performed through a photomask. The photomask may be, for example, a photomask having a desired pattern cut out. The material of the photomask is not particularly limited, but is preferably a material that blocks light of the wavelength. For example, a photomask having chromium as a light-shielding film is preferably used, but is not limited thereto.
[0087] (iii) After exposure, the film is developed with a developer to form a pattern. As the developer, for example, organic solvents such as alcohols such as IPA, ketones such as cyclohexanone, glycols such as propylene glycol monomethyl ether, and known alkaline developers such as an aqueous solution of tetramethylammonium hydroxide are preferred. As the development method, there are conventional methods such as a dip method in which a substrate on which a pattern has been formed is immersed in a developer, a paddle method in which a developer is dispensed with a paddle, and a spray method in which a developer is sprayed with a spray. By developing in this way, the non-exposed portion is dissolved and removed, and a pattern is formed. Thereafter, washing, rinsing, drying, etc. are performed as necessary to obtain a cured film having a desired pattern.
[0088] The pattern forming method using the photosensitive resin composition of the present invention allows easy formation of fine patterns. For example, the photosensitive resin composition of the present invention is formed into a film so as to cover a large number of blue micro LEDs arranged on a substrate, and then fine patterns are formed to form a cured film containing red and green quantum dots on each part of the blue micro LED, which can also emit red and green light, making it possible to fabricate a full-color light-emitting device.
[0089] [Light emitting element] The light-emitting device of the present invention is provided with a cured coating film obtained by the above-described pattern formation method. EXAMPLES
[0090] The present invention will be described in more detail below with reference to synthesis examples, examples, and comparative examples, but the present invention is not limited to the following examples. Note that InP / ZnSe / ZnS core-shell quantum dots are used as quantum dot materials, and the core synthesis method is as shown in [1-1] (red quantum dots) and [1-2] (green quantum dots) described later, and the subsequent shell synthesis method is as shown in [2].
[0091] [1-1] Red quantum dot core synthesis process Two flasks were prepared, and 0.23g (0.9mmol) of palmitic acid, 0.088g (0.3mmol) of indium acetate, and 10mL of 1-octadecene were added to each flask. The mixture was heated and stirred at 100℃ under reduced pressure, and degassed for 1 hour while dissolving the raw materials. Nitrogen was then purged into the two flasks, and 0.75mL (0.15mmol) of tristrimethylsilylphosphine / trioctylphosphine solution (0.2M) was added to both flasks. One flask was then heated to 300℃, and the solution was removed from the flask that was not heated and added to the flask heated to 300℃, producing core particles.
[0092] [1-2] Green quantum dot core synthesis process 0.23g (0.9mmol) of palmitic acid, 0.088g (0.3mmol) of indium acetate, and 10mL of 1-octadecene were added to the flask, and the mixture was heated and stirred at 100℃ under reduced pressure to dissolve the raw materials and degassed for 1 hour. After that, nitrogen was purged into the flask, and 0.75mL (0.15mmol) of a 0.2M solution of tristrimethylsilylphosphine and trioctylphosphine was added and the temperature was raised to 300℃ to generate core particles.
[0093] [2] Quantum dot shell layer synthesis process Next, 2.85g (4.5mmol) of zinc stearate and 15mL of 1-octadecene were added to another flask, and the mixture was heated and stirred at 100°C under reduced pressure. While dissolving, the mixture was degassed for 1 hour to prepare a 0.3M zinc stearate octadecene solution. 3.0mL (0.9mmol) was added to the reaction solution after the core synthesis and cooled to 200°C. Next, 0.474g (6mmol) of selenium and 4mL of trioctylphosphine were added to another flask, and the mixture was heated to 150°C and dissolved to prepare a 1.5M selenium trioctylphosphine solution. The reaction solution after the core synthesis step, which had been cooled to 200°C, was heated to 320°C over 30 minutes, and the selenium trioctylphosphine solution was added in 0.1mL increments to a total of 0.6mL (0.9mmol), and the mixture was held at 320°C for 10 minutes and then cooled to room temperature. 0.44g (2.2mmol) of zinc acetate was added and dissolved by heating and stirring at 100℃ under reduced pressure. The flask was purged again with nitrogen and heated to 230℃, and 0.98mL (4mmol) of 1-dodecanethiol was added and held for 1 hour. The resulting solution was cooled to room temperature to produce a core-shell quantum dot-containing solution. The red core-shell quantum dot-containing solution synthesized through steps [1-1] to [2] was designated R-1, and the green core-shell quantum dot-containing solution synthesized through steps [1-2] to [2] was designated G-1.
[0094] [3] Ligand exchange process (3-mercaptopropyl)triethoxysilane was used as a ligand having a substituent capable of forming a siloxane bond and a substituent that coordinates to the quantum dot surface. For the ligand exchange reaction, (3-mercaptopropyl)triethoxysilane (3.0 mmol) was added to the solution after the shell synthesis process that had been cooled to room temperature and stirred for 24 hours. After the reaction was completed, ethanol was added to precipitate the reaction solution, which was then centrifuged and the supernatant was removed. The same purification was performed again, and the solution was dispersed in toluene to prepare a quantum dot solution in which a ligand having a substituent capable of forming a siloxane bond was coordinated. The quantum dots synthesized using R-1 and R-2 were used to coordinate a ligand having a substituent capable of forming a siloxane bond, and the quantum dots synthesized using G-1 and G-2 were used to coordinate a ligand having a substituent capable of forming a siloxane bond.
[0095] [4-1] Surface coating layer formation process Triethoxysilylpropyl methacrylate (4.0 mmol), diphenylsilanediol (6 mmol), barium hydroxide monohydrate (0.15 mmol), and the quantum dot toluene solution after the ligand exchange process were added to a flask purged with nitrogen, and the mixture was heated and stirred at 65°C for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, ethanol was added to precipitate the reaction solution, and the mixture was centrifuged to remove the supernatant. The mixture was dispersed in toluene, and then PGMEA was added. The toluene solvent was removed by vacuum distillation to prepare a quantum dot solution with a surface coating layer (a solution with a solid concentration of 60%). The quantum dots with a surface coating layer formed using R-2 were designated RS, and the quantum dots with a surface coating layer formed using G-2 were designated GS.
[0096] [4-2] Surface coating layer formation process Triethoxysilylpropyl methacrylate (4.0 mmol), diphenylsilanediol (6 mmol), barium hydroxide monohydrate (0.15 mmol), and the quantum dot toluene solution after the ligand exchange process were added to a flask that had been purged with nitrogen, and the mixture was heated and stirred at 65°C for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, ethanol was added to precipitate the reaction solution, and the mixture was centrifuged and the supernatant was removed. The mixture was dispersed in toluene and added to a flask that had been purged with nitrogen in advance, and 2 parts by mass of (A) resin having a (meth)acryloyl group was added per 100 parts by mass of the quantum dot toluene solution. Furthermore, 1 part by mass of Irgacure 1173 was added per 100 parts by mass of resin having a (meth)acryloyl group, and after stirring and mixing, the mixture was irradiated with a UVLED irradiation device at a wavelength of 365 nm and an output of 4000 mW / cm. 2 The light was irradiated for 20 seconds. After the reaction was completed, ethanol was added to precipitate the mixture, and the supernatant was removed after centrifugation and dispersed in toluene again. Then, PGMEA was added, and the toluene solvent was removed by vacuum distillation to prepare a quantum dot solution (solid concentration 60% solution) with a surface coating layer. At this time, as the resin having (A) (meth)acryloyl groups, the product name "RA-4101" (Mw: 30,000, acid value: 90 mg KOH / g, double bond equivalent: 350) manufactured by Negami Chemical Industries Co., Ltd., the product name "8KQ-2001" (Mw: 20,000, acid value: 130 mg KOH / g, double bond equivalent: 540) manufactured by Taisei Fine Chemical Co., Ltd., and the product name "8KQ-7052" (Mw: 19,000, acid value: 7 mg KOH / g, double bond equivalent: 500) were used. Here, the quantum dots used to form a surface coating layer from the combination of R-2 and RA-4101 are referred to as R4101, the quantum dots used to form a surface coating layer from the combination of G-2 and RA-4101 are referred to as G4101, the quantum dots used to form a surface coating layer from the combination of R-2 and 8KQ-2001 are referred to as R2001, the quantum dots used to form a surface coating layer from the combination of G-2 and 8KQ-2001 are referred to as G2001, the quantum dots used to form a surface coating layer from the combination of R-2 and 8KQ-7052 are referred to as R7052, and the quantum dots used to form a surface coating layer from the combination of G-2 and 8KQ-7052 are referred to as G7052.
[0097] [5] Preparation of photosensitive resin composition and its evaluation [Examples 1 to 24 and Comparative Examples 1 to 24] Each component was blended according to the blending amounts shown in Tables 1 to 4, then stirred and mixed at room temperature and microfiltered through a 1.0 μm glass filter to obtain photosensitive resin compositions of Examples 1 to 24 and Comparative Examples 1 to 24.
[0098] [Table 1]
[0099] [Table 2]
[0100] [Table 3]
[0101] [Table 4]
[0102] In Tables 1 to 4, the resins are the trade names "RA-4101" (Mw: 30,000 g / mol, acid value: 90 mg KOH / g, double bond equivalent: 350 g / mol), "RA-3631P" (Mw: 18,000 g / mol, acid value: 5 mg KOH / g, double bond equivalent: 250 g / mol), and "8KQ-2001" (Mw: 20,000 g / mol, acid value: 130 mg KOH / g, double bond equivalent: 540 g / mol), and "8KQ-7052" (Mw: 19,000 g / mol, acid value: 7 mg KOH / g, double bond equivalent: 500 g / mol), manufactured by Negami Chemical Co., Ltd.
[0103] In Tables 1 to 4, the photoradical generators are "Irgacure184" (1-hydroxycyclohexyl-phenyl ketone) and "IrgacureOXE01", both manufactured by BASF. [ka]
[0104] In Tables 1 to 4, the surfactant is a product name "KP-341" (polyether type siloxane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0105] In Tables 1 to 4, the silane coupling agent is the product name "KBM-503" (3-methacryloxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0106] In Tables 1 to 4, the crosslinking agents are trade name "Aronix (registered trademark) M-940" (dipentaerythritol hexaacrylate) manufactured by Toagosei Co., Ltd., and trade name "DPCA-20" manufactured by Nippon Kayaku Co., Ltd. [ka]
[0107] In Tables 1 to 4, the quantum dots R-3 are S-BE030 manufactured by Shoei Chemical Co., Ltd. (particle size 5 to 10 nm, material InP:ZnS:SeZn = 25:50:25), R-4 are 900514-1ML manufactured by Aldrich (particle size 5 to 10 nm, material CdSe (core) / CdS (shell) core-shell type), G-3 are S-BE029 manufactured by Shoei Chemical Co., Ltd. (particle size 3 to 5 nm, material InP:ZnS:SeZn = 25:50:25), and G-4 are 900511-1ML manufactured by Aldrich (particle size 3 to 5 nm, material CdSe (core) / CdS (shell) core-shell type).
[0108] [6] Evaluation of photosensitive resin composition (1) Confirmation of aggregates in the film Each photosensitive resin composition was coated on a silicon wafer with a film thickness of 10 μm using a spin coater. In order to remove the solvent from the composition, the substrate was placed on a hot plate and heated and dried at 110° C. for 2 minutes. The agglomerates in the obtained photosensitive resin film were confirmed with an optical microscope, and the results are shown in Tables 5 to 8, with agglomerates of 1 μm or more in size observed in an area of 10 mm x 10 mm being marked with ×, and those without agglomerates or with a size of less than 1 μm being marked with ○.
[0109] (2) Pattern formation and its evaluation The obtained photosensitive resin film was exposed to light using an i-line stepper NSR-2205i11D (Nikon Corporation) through a mask to form a square island pattern with a pitch width of 1:1 with the adjacent pattern. After irradiation, paddle development was performed for 60 seconds with an aqueous solution of 2.38% tetramethylammonium hydroxide for the odd-numbered examples and comparative examples, and with PGMEA for the even-numbered examples and comparative examples, to form a pattern. Thereafter, the formed island patterns with sides of 50 μm, 30 μm, 20 μm, 10 μm, and 5 μm were observed with a scanning electron microscope (SEM), and the minimum pattern size that was not connected to the adjacent island pattern (pitch width of 1:1) was determined as the limiting resolution. In addition, those in which the resolution did not reach 50 μm or the pattern peeled off during development were marked with ×. The results are shown in Tables 5 to 8.
[0110] (3) Evaluation of the luminescence properties of the formed patterns Using LabRAM HR Evolution manufactured by Horiba Techno Service Co., Ltd., the patterned sample prepared in (2) above was irradiated with 457 nm laser light (0.03 mW), the photoconverted island pattern area was measured, and the emission intensity, emission wavelength, and half-width of the photoconverted light were measured. In addition, the sample prepared in (1) above after the heat drying process was similarly measured to measure the emission intensity of the photoconverted light. The results are shown in Tables 5 to 8 (M: million).
[0111] (4) Reliability test evaluation The patterned measurement sample in (3) above was also measured using an Atlas Suntest XLS+ manufactured by Toyo Seiki Seisakusho Co., Ltd. at an illuminance of 65 W / m 2 A sunlight resistance test was conducted for 300 hours at an environmental temperature of 100°C. The luminous intensity of the converted light was measured before and after the test in the same manner as in (3), and the rate of change (rate of decrease) from the initial value was confirmed. The results are shown in Tables 5 to 8. Rate of change = ((luminescence intensity after test / luminescence intensity before test)-1) x 100
[0112] [Table 5]
[0113] [Table 6]
[0114] [Table 7]
[0115] [Table 8]
[0116] The above results demonstrate that the photosensitive resin composition of the present invention can form a good photosensitive resin film free of aggregates (or if any, the aggregates are extremely small), and can provide a cured film (cured film) that has high lithography resolution, high luminescence characteristics that do not change before and after the lithography process, and good reliability (low rate of change in luminescence intensity in sunlight light resistance test), and is suitable for light-emitting devices.
[0117] The present specification includes the following aspects. [1]: A photosensitive resin composition comprising: (A) a resin having a (meth)acryloyl group, (B) a photoradical generator, and (C) Quantum dots wherein the quantum dots have a surface coating layer containing siloxane. [2]: The photosensitive resin composition according to the above [1], wherein the component (C) contains a skeleton having a (meth)acryloyl group in the surface coating layer. [3]: The photosensitive resin composition according to [1] or [2] above, characterized in that the quantum dots of component (C) have ligands coordinated to their surfaces, the surface coating layer contains siloxane bonds bonded to the ligands, and the substituents of the ligands have one or more of an amino group, a thiol group, a carboxy group, a phosphino group, a phosphine oxide group, and an ammonium ion. [4]: The photosensitive resin composition according to the above [1], [2] or [3], wherein the component (C) is contained in an amount of 5 to 80 mass % in the photosensitive resin composition. [5]: The photosensitive resin composition according to [1], [2], [3] or [4] above, wherein the double bond equivalent of the component (A) is 240 to 1,000 g / mol. [6]: The photosensitive resin composition according to [1], [2], [3], [4] or [5] above, characterized in that the weight average molecular weight Mw of the component (A) is 5,000 to 100,000 g / mol. [7]: The photosensitive resin composition according to [1], [2], [3], [4], [5] or [6] above, further comprising (D) a surfactant. [8]: The photosensitive resin composition according to [1], [2], [3], [4], [5], [6] or [7], further comprising (E) a silane coupling agent. [9]: The photosensitive resin composition according to [1], [2], [3], [4], [5], [6], [7] or [8], further comprising (F) a crosslinking agent having two or more (meth)acryloyl groups.
[10] : The photosensitive resin composition according to [1], [2], [3], [4], [5], [6], [7], [8] or [9], further comprising (G) a solvent.
[11] : A photosensitive resin film, which is a dried product of the photosensitive resin composition according to [1], [2], [3], [4], [5], [6], [7], [8], [9] or
[10] .
[12] : A pattern forming method comprising the steps of: (i) applying the photosensitive resin composition of [1], [2], [3], [4], [5], [6], [7], [8], [9] or
[10] above onto a substrate to form a photosensitive resin film on the substrate; (ii) exposing the photosensitive resin film to light; and (iii) A step of developing the exposed photosensitive resin film with a developer to dissolve and remove the non-exposed areas to form a pattern. A pattern forming method comprising the steps of:
[13] : A light-emitting device comprising a cured coating obtained by the pattern formation method according to
[12] above.
[0118] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.
Claims
1. A photosensitive resin composition comprising: (A) a resin having a (meth)acryloyl group, (B) a photoradical generator, and (C) Quantum dots wherein the quantum dots have a surface coating layer containing siloxane.
2. 2. The photosensitive resin composition according to claim 1, wherein the component (C) contains a skeleton having a (meth)acryloyl group in the surface coating layer.
3. The photosensitive resin composition according to claim 1, characterized in that the quantum dots of the component (C) have ligands coordinated to their surfaces, the surface coating layer contains siloxane bonds bonded to the ligands, and the substituents of the ligands have one or more of an amino group, a thiol group, a carboxy group, a phosphino group, a phosphine oxide group, and an ammonium ion.
4. 2. The photosensitive resin composition according to claim 1, wherein the component (C) is contained in an amount of 5 to 80% by mass in the photosensitive resin composition.
5. 2. The photosensitive resin composition according to claim 1, wherein the component (A) has a double bond equivalent of 240 to 1,000 g / mol.
6. 2. The photosensitive resin composition according to claim 1, wherein the weight average molecular weight Mw of the component (A) is 5,000 to 100,000 g / mol.
7. 2. The photosensitive resin composition according to claim 1, further comprising (D) a surfactant.
8. 2. The photosensitive resin composition according to claim 1, further comprising (E) a silane coupling agent.
9. 2. The photosensitive resin composition according to claim 1, further comprising (F) a crosslinking agent having two or more functional (meth)acryloyl groups.
10. 2. The photosensitive resin composition according to claim 1, further comprising (G) a solvent.
11. A photosensitive resin film, which is a dried product of the photosensitive resin composition according to any one of claims 1 to 10.
12. A pattern formation method comprising the steps of: (i) applying the photosensitive resin composition according to any one of claims 1 to 10 onto a substrate to form a photosensitive resin film on the substrate; (ii) exposing the photosensitive resin film to light; and (iii) A step of developing the exposed photosensitive resin film with a developer to dissolve and remove the non-exposed areas to form a pattern. A pattern forming method comprising the steps of:
13. A light-emitting device comprising a cured film obtained by the pattern formation method according to claim 12.